2019
DOI: 10.1111/cpr.12640
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 accelerates the development and progression of renal cell carcinoma by decreasing the expression of miR‐203 and promoting the expression of BIRC5

Abstract: | INTRODUC TI ONRenal cell carcinoma (RCC) is a common cancer that accounts for 2%-3% of all cancerous diseases in adults. 1 There are approximately 65 000 cases of RCC each year, and RCC is the eighth most common cause of cancer mortality. 2 RCC affects quality of life and life expectancy and has important health and economic implications related to metabolic syndromes, increased cardiovascular risk and end-stage kidney disease. 3 In addition, clear cell renal cell carcinoma (ccRCC) is the most universal subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 37 publications
4
58
0
1
Order By: Relevance
“…The oncogenic role of MALAT1 in the progression of human cancers has gradually emerged. For instance, Zhang et al announced that MALAT1 accelerated the progression of renal cell carcinoma via the regulation of the miR-203/BIRC5 axis (Zhang et al 2019). Sun et al claimed that MALAT1 expression was elevated and regulated cell proliferation and apoptosis in ovarian cancer through directly targeting miR-503-5p (Sun et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of MALAT1 in the progression of human cancers has gradually emerged. For instance, Zhang et al announced that MALAT1 accelerated the progression of renal cell carcinoma via the regulation of the miR-203/BIRC5 axis (Zhang et al 2019). Sun et al claimed that MALAT1 expression was elevated and regulated cell proliferation and apoptosis in ovarian cancer through directly targeting miR-503-5p (Sun et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, a multitude of researches claimed that lncRNA could function as a competitive endogenous RNA (ceRNA) by sequestering micro RNA (miRNA) to release target gene, and thereby modulate the biological processes in tumors. For instances, MALAT1 accelerates cell proliferation and migration of renal cell carcinoma cells by sponging miR-203 and increasing BIRC5 expression [16]. SNHG5/miR-26a/SOX2 axis promotes proliferation of chondrocyte in osteoarthritis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [25] found that lncRNA AB209371 accelerated the development and progression of ovarian carcinoma by suppressing miR-203 expression. MALAT1 promoted the development of renal cell carcinoma by reducing the expression of miR-203 expression [26]. Furthermore, miR-203 has been proven to be involved in the expression of several cancerrelated factors.…”
Section: Discussionmentioning
confidence: 99%